BEKERJA DALAM PANDANGAN EKONOMI ISLAM: SEBUAH KAJIAN SECARA TEMATIK HADITS NABI MUHAMMAD SAW - Syaidun Syaidun (Investama : Jurnal Ekonomi dan Bisnis, 2023)
In the Islamic economic system, work is not seen as the main driving force ineconomic activity, but work is a very noble deed in the context of realizing benefit both individually and in society. While working in the Islamic economic system is a must and a syara' obligation and is also seen as a form of worship for the perpetrators. And all forms of unemployment, and begging is a despicable acts. So work gets very special attention both in the Qur'an and in the Hadith of the Prophet Muhammad.